Essential Oil Content of the Rhizome of Curcuma purpurascens Bl. (Temu Tis) and Its Antiproliferative Effect on Selected Human Carcinoma Cell Lines - Sok-Lai Hong; Guan-Serm Lee; Syarifah Nur Syed Abdul Rahman; Omer Abdalla Ahmed Hamdi; Khalijah Awang; Nurfina Aznam Nugroho; Sri Nurestri Abd Malek (The Scientific World Journal)
Curcuma purpurascens Bl., belonging to the Zingiberaceae family, is known as temu tis in Yogyakarta, Indonesia. In this study, the hydrodistilled dried ground rhizome oil was investigated for its chemical content and antiproliferative activity against selected human carcinoma cell lines (MCF7, Ca Ski, A549, HT29, and HCT116) and a normal human lung fibroblast cell line (MRC5). Results from GC-MS and GC-FID analysis of the rhizome oil of temu tis showed turmerone as the major component, followed by germacrone, ar-turmerone, germacrene-B, and curlone. The rhizome oil of temu tis exhibited strong cytotoxicity against HT29 cells (IC50 value of 4.9 ± 0.4 μg/mL), weak cytotoxicity against A549, Ca Ski, and HCT116 cells (with IC50 values of 46.3 ± 0.7, 32.5 ± 1.1, and 35.0 ± 0.3 μg/mL, resp.), and no inhibitory effect against MCF7 cells. It exhibited mild cytotoxicity against a noncancerous human lung fibroblast cell line (MRC5), with an IC50 value of 25.2 ± 2.7 μg/mL. This is the first report on the chemical composition of this rhizome’s oil and its selective antiproliferative effect on HT29. The obtained data provided a basis for further investigation of the mode of cell death.